Effects of accuracy of incentive weights when rewarding non-financial value drivers. - Khim, Kelly. (2008)
I use an experiment to examine how the accuracy of relative incentive weights on non-financial value drivers in incentive contracts affect managerial performance in firms where intangible assets are more important than tangible assets for future financial performance. Rewarding non-financial value drivers with a summary financial measure improves performance over time regardless of the accuracy of the relative incentive weights on the non-financial value drivers. However, when only non-financial value drivers are rewarded, performance improves over time if they are accurately-weighted but decreases over time if they are inaccurately-weighted. When non-financial value drivers are accurately-weighted, managerial performance is better rewarding only the non-financial value drivers than rewarding both the non-financial value drivers and the summary financial measure. Conversely, when non-financial value drivers are inaccurately-weighted, managerial performance in the long run is better rewarding both the non-financial value drivers and the summary financial measure than rewarding only the non-financial value drivers. These results suggest that continuing to reward a summary financial measure may prevent performance decline when the relative incentive weights on non-financial value drivers are inaccurate. Keywords: value driver; non-financial performance measure; incentive weights.